Representations about discrimination practices in the education system built by Russian and Ukrainian immigrants' children in Lisbon Metropolitan area - Mendes, M. M. (Trames, 2009)
Based on a thorough qualitative study and interviews, this study presents a brief portrait of Russian and Ukrainian immigrants settled in the Lisbon Metropolitan Area (Portugal), with a particular focus on social representations and emotions that emerged in discriminatory contexts related with the educational system. Besides some initial difficulties and problems experienced by the immigrant's descendents, in general they actually have a successful insertion in the education system.